Avaliação da tolerância à glicose, sensibilidade à insulina e parâmetros oxidativos em ratos submetidos à restrição proteica - Finger, Larissa (2014)
The reduction in protein intake and the increase in carbohydrate intake feature a dietary pattern present in the current lifestyle of the population worldwide, and it is associated with the incidence of pathologies such as diabetes mellitus, obesity and high blood pressure among others. Low protein intake is also associated with the development of oxidative stress, which contributes to the establishment of tissue lesions that may result in functional impairment of various organs. In view of these facts, this study aimed to investigate the possible renal damages caused by the administration of a hypoproteic-hyperglycemic diet to rats in the early growth stages. Male Wistar rats (~30 days and 100g) were divided into the following groups: 1) Control, fed on a diet containing 17% protein and 63% carbohydrates for 15 (C15) or 45 (C45) days; 2) LPHC, fed on a diet containing 6% protein and 74% carbohydrates for 15 (LPHC15) or 45 (LPHC45) days, and 3) reversal group, fed on a LPHC diet during 15 days and then fed on a control diet for the following 30 days (R45). Glucose tolerance (GTT) was assessed by the areas under glycemic curves (AUC) obtained by the Trapezoidal Rule and insulin tolerance (ITT) was calculated according to the serum glucose decline rate constant (Kitt). Oxidative stress was evaluated by quantifying the lipid peroxidation level through the dosage of MDA (malondialdehyde) in kidneys, levels of GSH (reduced glutathione) and by determining the activity of the enzymes GPx (glutathione peroxidase), GR (glutathione reductase), catalase and SOD (superoxide dismutase) in the kidneys as well as quantifying the total antioxidant capacity (TAC) in plasma. The renal function was evaluated by the quantification of plasma creatinine and histological analysis. Results were expressed as the mean ± SEM, and statistical comparisons were carried out by means of the Student t Test or one-way ANOVA, followed by Tukey’s post-test (p < 0,05). LPHC15 animals presented similar values to those of the C15 group in reference to GSH, GPx, GR, SOD and catalase. However, the weight of kidneys (C15: 5,59 ± 0,21; LPHC15: 4,60 ± 0,08 mg / g body weight) and TAC values (C15: 0,486 ± 0,059; LPHC5: 0,252 ± 0,059 mmol/L) were lower, while plasma creatinine (C45: 0,672 ± 0,028; LPHC45: 1,003 ± 0,039 mg/dL) and MDA level (C15: 0,0195 ± 0,001; LPHC15: 0,033 ± 0,001 mmol/g tissue) were higher for the LPHC15 group compared with C15. After administering the LPHC diet for 45 days, the values for fasting glycemia in C45 and LPHC45 animals were similar. However, the glycemia level of R45 animals was 11% (p < 0,05) higher than in the other groups. There were no differences in the AUC between groups analyzed for GTT. The same happened when plasma glucose decline was analyzed following insulin administration. The activity of SOD and catalase enzymes was similar in the three groups under evaluation, whereas the activity of GPx (C45: 2,730 ± 0,732; LPHC45: 0,928 ± 0,176; R45: 3,290 ± 0,304 U/mg protein) and GR (C45: 2,730 ± 0,732; LPHC45: 0,928 ± 0,176; R45: 3,290 ± 0,304 U/mg protein) was lower in the LPHC45 group. GSH concentration was lower in the R45 group (C45: 0,785 ± 0,034; LPHC45: 0,760 ± 0,047; R45: 0,510 ± 0,024 mmol/g of tissue). The level of MDA was higher in the LPHC45 and R45 groups (C45: 11,170 ± 2,020; LPHC45: 31,030 ± 3,060; R45: 31,540 ± 4,460 mmol/g of tissue). The weight of kidneys (C45: 3,72 ± 0,03; LPHC45: 3,17 ± 0,05; R45: 3,66 ± 0,09) and TAC (C45: 0,583 ± 0,059; LPHC45: 0,135 ± 0,050; R45= 0,407 ± 0,108 mmol/L) showed lower values in the LPHC45 group. LPHC45 and R45 groups presented higher levels of plasma creatinine (C45: 0,556 ± 0,020; LPHC45: 0,640 ± 0,021; R45: 0,678 ± 0,023 mg/dL). Histological analysis showed interstitial lipid deposition in kidneys for LPHC45 and R45 groups, graded from mild to marked. These data lead to the conclusion that the LPHC diet, when introduced immediately after weaning and administered along 45 days, does not alter either glucose tolerance or insulin sensitivity. This conclusion is different from what was concluded in a previous study where LPHC diet administered during 15 days resulted in greater insulin sensitivity. Yet protein restriction, introduced soon after weaning, has led to damage in kidney development, which may result in impaired renal function associated to increased fat deposition and oxidative stress. Even though the diet reversal may recover kidney weight, the increased levels of serum creatinine and higher content of MDA in the organ suggest that functional damages resulting from oxidative stress are irreversible.